Comparison Of Calligraphy Learning Methods of Traditional Boarding School Al-Ansor and Modern Boarding School Darul Hikmah TPI Medan-North Sumatera - Rahma Aswani (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Traditional boarding schools are learning institutions that use classical books such as the yellow book to serve as learning guidelines. Meanwhile, modern boarding schools are boarding schools that are more dominant to general learning, but these two boarding schools still study calligraphy. Calligraphy is a science that studies the beauty of the art of writing in Islam. The purpose of this research is to find a comparison of calligraphy learning methods in traditional boarding schools and modern boarding schools. This research method uses observation techniques, interviews, and literature sources, where researchers record all information during the research. The results of this study indicate that calligraphy learning is still a subject of interest to students in both traditional and modern boarding schools. However, traditional and modern pesantren do not really focus on calligraphy learning.